Retroperitoneal Laparoscopic Ureterolithotomy for Proximal Ureteral Calculi in Selected Patients - Qingfeng Hu; Weihong Ding; Yuancheng Gou; Yatfaat Ho; Ke Xu; Bin Gu; Chuanyu Sun; Guowei Xia; Qiang Ding (The Scientific World Journal)
Objectives. To summarize our experience of retroperitoneal laparoscopic ureterolithotomy for ureteral calculi and evaluate the safety and efficiency of this procedure. Methods. We conducted a retrospective analysis of 197 patients with proximal ureteral calculi who accepted retroperitoneal laparoscopic ureterolithotomy from June 2005 to June 2014. Results. All procedures were performed successfully and the mean operating time and estimated blood loss were 87 min and 64 mL. The clearance rate was 98.5% and the rates of urine leak and ureteral stricture were 2.5% and 1.0%. Conclusions. Retroperitoneal laparoscopic ureterolithotomy is a safe and effective procedure for patients with complex stones or anatomic abnormalities, and, with experience of high volume series, it is also a reasonable choice as the primary treatment for such selected patients.